PENGARUH LATIHAN PASSING PINTU KE PINTU TERHADAP KETERAMPILAN PASSING SSB ASAM JAWA USIA 12 TAHUN KABUPATEN LABUHANBATU SELATAN SUMATERA UTARA - Jaetu Saheru; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is "The Effect of Passing Door to Door Training on Passing Skills SSB Asam Jawa 12 Years Old South Labuhanbatu District of North Sumatra" So that athletes can play much better in the future and especially after research and find out if there is an increase in passing skills in football games to balance the opponent's game and achieve maximum results in the future. The form of this study is using the only group of preetest-posttest design approach) with the population of football players in the SSB Asam Jawa 12 Years Old South Labuhanbatu District of North Sumatra. The data in this study are all populations of 18 people. The instrument used in this study used the Short Pass test, which aims to determine The Effect of Passing Door to Door Training on Passing Skills SSB Asam Jawa 12 Years Old South Labuhanbatu District of North Sumatra. The data were then processed with statistics to test the normality using the liliefors test at a significant level of 0.05 α. The proposed hypothesis is there The Effect of Passing Door to Door Training on Passing Skills SSB Asam Jawa 12 Years Old South Labuhanbatu District of North Sumatra. Based on the normal test analysis, data X produces Lcount of 0.1498 and Ltable of 0.200, which means Lcount < Ltable. While Y variable produces Lcount equal to 0.1466 and Ltable equals 0.200. This means Lcount < Ltable. There are averages based on the analysis of statistical data variable X 70,11 and the average variable Y is 82,89, then the data is normally distributed. So there is The Effect of Passing Door to Door Training on Passing Skills SSB Asam Jawa 12 Years Old South Labuhanbatu District of North Sumatra.Key Words: Passing Door to Door Training, Passing Skills.